Using Dried Blood Spots for a Sero-Surveillance Study of Maternally Derived Antibody against Group B Streptococcus - Erick Auma; Tom Hall; Simran Chopra; Sam Bilton; Laxmee Ramkhelawon; Fahimah Amini; Anna Calvert; Gayatri Amirthalingam; Christine E. Jones; Nick Andrews; Paul T. Heath; Kirsty Le Doare (Vaccines, 2023)
Vaccination during pregnancy could protect women and their infants from invasive Group B Streptococcus (GBS) disease. To understand if neonatal dried blood spots (DBS) can be used to determine the amount of maternally derived antibody that protects infants against invasive GBS disease, a retrospective case-control study was conducted in England between 1 April 2014 and 30 April 2015. The DBS of cases with invasive GBS disease (n = 61) were matched with healthy controls (n = 125). The haematocrit, DBS storage temperature, freeze-thaw cycle, and paired serum/DBS studies were set up to optimise the antibody assessment. The samples were analysed using a multiplex immunoassay, and the results were assessed using parametric and nonparametric tests. Antibody concentrations were stable at haematocrits of up to 50% but declined at 75%. DBS storage at room temperature was stable for three months compared with storage from collection at −20 °C and rapidly degraded thereafter. Total IgG levels measured in DBS and paired serum showed a good correlation (r2 = 0.99). However, due to suboptimal storage conditions, no difference was found in the GBS IgG levels between DBS samples from cases and controls. We have demonstrated a proof of concept that assays utilising DBS for assessing GBS serotype-specific antibodies in infants is viable. This method could be used to facilitate future large sero-correlate studies, but DBS samples must be stored at −20 °C for long term preservation of antibody.